Pengukuran Kinerja Rantai Pasok Berbasis Model SCOR Menggunakan Metode OMAX-TLS di Industri Pembuatan Kemasan Produk - Vivi Arisandhy; David Try Liputra; Victor Suhandi; Yonathan Yehezkiel Widjaja; Nadia Natalia Suwandi (Universitas Teuku Umar, 2026)
Industrial development in the era of globalization is progressing very rapidly and is accompanied by increasing competition between companies. To maintain high competitiveness in meeting market needs, a company's operational performance must continue to improve. Research on measuring supply chain performance has been widely conducted. However, research using a combination of the SCOR model and the Objective Matrix (OMAX) and Traffic Light System (TLS) method is still limited. Therefore, in this study, a combination of the Supply Chain Operations Reference (SCOR) model with the OMAX-TLS methods will be used to measure the supply chain performance of a product packaging company. This study uses the SCOR model with weights from the Analytical Hierarchy Process (AHP) and then measures it with OMAX and TLS for performance evaluation in product packaging companies. Performance measurement is needed to improve supply chain performance. Data processing uses 29 performance indicators to measure supply chain performance. The results obtained are supply chain performance at 6.826, indicating Good performance. Indicators with a score below 3 are included in the Poor category. There are two performance indicators in the Poor category, twenty in the Good category, and seven in the Very Good category. Performance indicators that require significant improvement are indicators that fall into the Poor category.